Mathematical modelling of sediment dynamics and their deposition in Lithuanian rivers and their deltas (case studies) - Vaikasas, Saulius (Journal of Environmental Engineering and Landscape Management, 2010)
Mathematical modelling of sediment transport and deposition in the floodplains and canals of rivers is closely related to the hydrodynamics, as well as the design of engineering measures, of water pollution control and reduction. The dynamics of flow velocities and water level in the urban section of the Nevežis River at Kedainiai were estimated by applying a hydraulic‐mathematical model, DELTA. It was established that there were no conditions for undesirable river‐bed siltation. During the dry season (Qv.f = m3/s), flow velocity did not exceed 0.5 m/s in the study section. When the discharge affected the formation of the riverbed (Qv.f = 70 m3/s), the flow velocity reached 1.2–1.3 m/s and accumulated bed sediments were washed away. A two‐meters high dam near Skongalis does not stimulate bed silting, as it is not high enough to have much influence on the bed formation processes or the reduction of riverside overgrowth. When the water level is low and the flow velocity is small (0.1 m/s), the water in the river is only slightly turbid (turbidity is 2–6 mg/l), so there is no scope to decrease sedimentation in this case. To improve the aesthetical view of the river, it is advisable to regulate the riverbed by reducing the river width to a 30 m maximum. Floods in the Nemunas delta inundate the bright areas of the valley, where the significant amount of sediments brought by the water is deposited. This decreases the water pollution entering the Curonian Lagoon and the Baltic Sea. It is, therefore, desirable to find ways to intensify this deposition and to put them into practice. The possibility of increasing the discharge of water flowing through the flood plane was investigated, applying the DELTA model. The influences of road banks built across the floodplain and the growth of bushes in the valley were tested. They cause increases in depth and decreases in flow velocity, which can alter the amount of sediment deposition. Article in Lithuanian. Skendinčiųjų nešmenų ir nuosėdų dinamikos kai kurių Lietuvos upių vagose ir deltose modeliavimas Santrauka. Upių taršos mažinimo inžinerinių priemonių projektavimas ir jų būklės kontrolė įmanoma tik matematiškai sumodeliavus skendinčiųjų nešmenų hidrodinamiką bei ištyrus tų priemonių veiksmingumą taršai sumažinti ir nešmenims nusodinti. Tam Nevėžio reguliuotoji atkarpa Kėdainiuose ir Nemuno užliejama delta ties Pagėgiais buvo ištirtos taikant hidraulinį matematinį modelį DELTA. Nustatyta, kad Nevėžio vaga, nepaisant jos mažų debitų sausmečiu (Q s.p.v ≈ 3 m3/s) ir greičiu (v ≤ 0,5 m/s), nedumblėja. Taip yra dėl to, kad per potvynius, kai upės vagą formuojantys debitai Q v.f = 70 m3/s, o tėkmes greičiai dideli (v = 1,2–1,3 m/s), anksčiau nusėdęs dumblas periodiškai išplaunamas ir išnešamas į slėnį bei žemupį. Dvimetrinis vandens paimos slenkstis ties Skongaliu taip pat šio proceso neveikia, nes per potvynį yra apsemiamas. Vasarą čia vandens lygiai žemi, o tėkmės greičiai ne didesni kaip 0,1 m/s, todėl Nevėžio vanduo palyginti skaidrus (drumstumas 2–6 mg/l), o jo skendinčiųjų nešmenų reguliavimo priemonės gali būti konstruktyvios arba visai nereikalingos. Iš skaičiavimų akivaizdu, kad per potvynius Nemuno deltoje nemažai anksčiau atneštų skendinčiųjų nešmenų kartu su vandeniu išplukdoma į slėnį ir jame nusėda. Dėl čia sulaikomų nešmenų sumažėja vandens, patenkančio į Kuršių marias ir Baltijos jūrą, drumstumas ir biogeninė tarša. Taigi reiketų didinti išsiliejančius į slenius potvynių debitus ir jų išnešamų skendinčiųjų nešmenų nusodinimą. Straipsnyje aptartas įvairių slėnio tėkmių debitų ir greičių reguliavimo priemonių – senvagių atverimo bei gilinimo, slėnį pertveriančių kelio pylimų įrengimo ir krūmų bei medžių užauginimo efektyvumas skendintiesiems nešmenims sulaikyti. Reikšminiai žodžiai: hidraulinis modeliavimas, vaginiai procesai, užliejami slėniai, nešmenų reguliavimas. Моделирование динамики влекомых наносов в некоторых руслах и низовьях рек Литвы Резюме. Проектирование инженерных средств для регулирования загрязнения рек и определение их эффективности возможно лишь при математическом моделировании гидродинамики и осаждения влекомых наносов. С этой целью при помощи двухмерной математической модели DELTA был исследован участок реки Нявежис в городе Кедайняй и дельта реки Нямунас у поселка Пагегяй. Установлено, что несмотря на сравнительно малые расходы воды в межсезонный период (Qs.p.v ≈ 3 м3 /с) и скорости течения (v ≤ 0,5 м/с), в русле р. Нявежис ил и взвешенные наносы не скапливаются, так как они регулярно выносятся во время паводков при наличии руслоформирующего расхода (Qv.f = 70 м3 /с) и возросших скоростях (v = 1,2–1,3 м/с). Влияние подтопления двухметрового порога у Сконгалис в это время ничтожно, а сам порог бывает полностью подтоплен. При помощи расчетов на модели DELTA также установлено, что значительная часть влекомых наносов в низовья р. Нямунас может быть осаждена и задержана при их выносе паводковыми течениями на периодически затопляемую дельту. Осаждаемая часть зависит от распределения расходов между основным руслом и поймой. Поэтому необходимо увеличивать выливание воды в пойму. В статье приведены результаты математического моделирования эффективности различных средств регулирования воды: открытия и углубления старых русел и вымоин, устройства дамб, дорожных насыпей в пойме, уменьшения скоростей течения при помощи посадки кустарников и деревьев в виде полос. Ключевые слова: гидравлическое моделирование, русловые процессы, затопление поймы, регулирование наносов. First Publish Online: 10 Feb 2011